Sugar-based beverage taxes and beverage prices: Evidence from South Africa's Health Promotion Levy. (October 2019) - Stacey, Nicholas; Mudara, Caroline; Ng, Shu Wen; van Walbeek, Corné; Hofman, Karen; Edoka, Ijeoma
Abstract: A growing number of jurisdictions are introducing taxes on sugar-sweetened beverages (SSBs) in efforts to reduce sugar intake, obesity, and associated metabolic conditions. A key dimension of the impact of such taxes is how they induce changes in the prices of the taxed beverages and their un-taxed substitutes. At present these taxes have typically been based solely on volume. More recently, however, due to the potential to target the source of SSBs' health harms and to incentivize product reformulation, SSB taxes are being levied based on sugar content. In April of 2018 South Africa implemented such a tax, the Health Promotion Levy (HPL), at a rate of 0.021 ZAR (approximately 0.15 US cents) for each gram of sugar over an initial threshold of 4 g/100 ml. Drawing on a dataset of price observations (N = 71, 677) collected in South Africa between January 2013 and March 2019, we study changes in beverage prices following the introduction of the HPL. We find null price increases among un-taxed beverages and find significant price increases for carbonates, the largest taxed product category. However, within carbonates we find similar increases in price for low- and high-sugar brands, despite the underlying difference in tax liability. In addition, while we find evidence of product reformulation, we find significant price increases among the brands that reduced their sugar content. While the findings are broadly consistent with the price changes of volume-based SSB taxes, future considerations of price effects of sugar-based SSB taxes need to account for the opportunity for intra-firm heterogeneity in price response among large multi-product firms. Highlights: In April of 2018, South Africa implemented a tax on sugar-sweetened beverages. Prices of carbonates increased by 1.006 ZAR/litre post the introduction of the tax. Prices of untaxed beverages did not increase. Among carbonates, price increases were not greater for higher sugar beverages.